Mandatory CSR Disclosure and its Insurance Effect: Evidence from China - He, Xinmeng; Li, Antai; Zhu, Keda (International Journal of Economics and Financial Issues, 2020)
China Securities Regulatory Commission (CRSC) requires listed companies to issue CSR report mandatorily from 2008. To examine the effect of mandatory CSR disclosure, we adopt the PSM-DID introduced by the mandatory requirements. We find that mandatory disclosure reduces stock return and increases stock volatility. We further investigate the insurance effect of CSR. After the requirement changes, firms are more regulates its behavior by reducing violation cost in the stock market and increasing environmental protection expenditure, especially in State-Owned Enterprises. It indicates that Insurance Effect of CSR can serve a good role in building a social and environmentally friendly society despite mandatory CSR disclosure hampers its financial performance. Keywords: Corporate social responsibility; Insurance effect; Mandatory disclosure. JEL Classifications: G14; G18; G38; L78 DOI: https://doi.org/10.32479/ijefi.10657